Flux - Quek, Pin Yi (Nanyang Technological University, 2020)
Flux is an experiential system that is designed to inculcate an awareness of the impermanence of things and the ephemeral quality of time and environment. Amalgamating artificiality and naturality, this project leverages technology and takes its cue from biophilic design principles; it uses generative visual design as a mechanism to build a visual narrative of the concept of transience and impermanence. Taking context from an ever-changing and urbanised world, the project aims for its viewers to contemplate the phenomenon of transience. The Flux experience seeks to encourage them to understand and appreciate change, serving to alleviate the stress encountered in a fast-paced environment.